Multifaceted Interplay between Mobile Edge Computing based on Industry 5.0 in Transportation - Noori, Salar Faisal; Yuvaraj, D.; Abas, Shakir Mahoomed; Sivaram, M.; Porkodi, V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
A new technology called mobile edge computing, or MEC, is now acknowledged as a crucial 5G network enabler. The demand for computation-intensive mobile network applications—which call for greater storage, potent machines, and real-time responses—has increased significantly in recent years. Because they must support many services, including traffic monitoring or data sharing involving various aspects of vehicular traffic, transportation systems play a crucial part in this ecosystem. Furthermore, new resource-hungry applications like in-car entertainment and self-driving cars have been imagined, making the need for processing and storage resources one of the biggest problems facing transportation networks. With the advent of multi-access edge computing (MEC) technological advances, real-time, high-bandwidth, minimal latency access to radio network resources is intended to be made possible by bringing cloud computing capabilities to the edge of the wireless access network. With MEC’s capacity to offer cloud computing and gateways capabilities at the network edge, IoT is recognized as a major application case for the technology. Because of its extensive mobility support and dense geographical spread, MEC will stimulate the development of a wide range of apps and services that require ultralow latencies and high quality of service. For this reason, MEC is a crucial enabler of Internet of Things services and applications that need immediate operation. At last, the globally ideal answer has been achieved. The suggested strategy is superior, as shown by the simulation results.